Anaerobic circulating liquid cell and in-situ electrocatalytic characterization method for high-resolution X-ray diffraction using horizontal goniometers

By designing an oxygen-free circulating liquid cell adapted to a horizontal goniometer and a precise calibration method, the problems of signal loss and leakage in oxygen-sensitive electrochemical systems were solved, achieving high-resolution electrochemical structural characterization, which is applicable to electrocatalytic processes of various sample forms.

CN121090582BActive Publication Date: 2026-01-30WESTLAKE UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511639587.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-11
Publication Date
2026-01-30
Estimated Expiration
2045-11-11

AI Technical Summary

Technical Problem

Existing technologies for in-situ XRD testing in oxygen-sensitive electrochemical systems face challenges such as insufficient sealing, leakage risk, signal loss due to window thickness, and data contamination by parasitic currents, making it impossible to achieve high-resolution structural characterization.

Method used

An oxygen-free circulating liquid pool was designed, which is compatible with the vertical installation of a horizontal goniometer. It adopts a thin-gauge Kapton membrane and a sealing screw, combined with electrolyte pre-deoxygenation and precise XRD optical path calibration to achieve isolation between the liquid path and the circuit. It is compatible with the high-resolution X-ray diffraction of the horizontal goniometer and conducts conductivity tests simultaneously.

Benefits of technology

It achieves high-precision structure tracking in oxygen-sensitive electrochemical processes, reduces X-ray absorption, improves signal-to-noise ratio and measurement accuracy, provides an in-situ environment for multi-field coupling, and is suitable for characterizing electrocatalytic processes of various sample morphologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121090582B_ABST
    Figure CN121090582B_ABST
Patent Text Reader

Abstract

This invention discloses an oxygen-free circulating liquid cell for high-resolution X-ray diffraction (XRD) using a horizontal goniometer and a method for in-situ detection and characterization of structural evolution during electrocatalysis. It aims to address the limitations of existing technologies, such as the inability to vertically install the in-situ cell, insufficient oxygen control, and limited characterization dimensions, thus hindering the accurate tracking of the microstructure evolution of functional thin films during oxygen-sensitive electrochemical processes. The liquid cell includes a vertically mounted adapter structure, a sealing screw with an integrated elastic conductive component and a liquid-electric isolation component, and an X-ray window using a 10-100 μm Kapton membrane, with a conductivity detection interface. The method includes cell assembly and leak detection, electrolyte inert gas deoxygenation circulation, XRD optical path calibration, and simultaneous application of an external electric field to acquire electrochemical, XRD, and conductivity data. This invention achieves angstrom-level structural monitoring, complete oxygen isolation, multi-dimensional characterization, and compatibility with thin film / bulk / powder samples deposited on substrates, filling a technological gap and contributing to device development in the energy and electronics fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the interdisciplinary field of materials characterization and electrochemical analysis, and specifically relates to an apparatus and testing method for in-situ high-resolution X-ray diffraction (XRD) analysis of electrochemical processes in a thin-layer flowing liquid environment under inert gas protection. Background Technology

[0002] In cutting-edge technology fields such as solid-state batteries, semiconductor devices, and electrocatalysis, the microstructure evolution of functional thin-film materials during electrochemical reactions is crucial to their performance. To track these structural changes in real time, in-situ X-ray diffraction (XRD) technology is widely used, which can dynamically monitor changes in the crystal structure of materials under real-world conditions where electric fields are applied or chemical reactions occur.

[0003] However, existing technologies face significant challenges when applied to oxygen-sensitive electrochemical systems, such as redox reactions involving proton migration. First, conventional in-situ liquid cells lack sufficient sealing to effectively isolate oxygen from the ambient atmosphere, leading to dissolved oxygen involvement in side reactions. This not only interferes with the main electrochemical process but also obscures the correlation between structural evolution and electrochemical response. Second, for horizontal goniometers commonly used in high-resolution XRD equipment, the in-situ cell requires vertical installation, posing a potential risk of leakage. In this unconventional installation, the flow rate of the circulating electrolyte into the sealed cavity must be carefully controlled, as the liquid pressure causes the flexible Kapton film, which serves as the X-ray window, to expand outwards. This minute deformation alters the precise geometric relationship between the sample surface and the X-ray path, resulting in diffraction signal distortion and rendering the test impossible. Third, traditional line light sources have a certain divergence, causing the light source to irradiate the surrounding area, leading to the inaccurate reception of stray signals. Therefore, we chose a point light source. In addition, some existing commercial in-situ cells have design flaws. For example, their conductive components are in direct contact with the electrolyte, which can easily cause parasitic currents and side reactions, contaminating experimental data. At the same time, the X-ray windows they use are too thick, resulting in extremely high X-ray absorption rates (some up to 95%), which severely weakens the diffraction signal and reduces the signal-to-noise ratio and measurement accuracy.

[0004] Therefore, there is an urgent need to develop an in-situ XRD characterization system and supporting methods that can effectively isolate oxygen, be compatible with vertical installation, and solve the problem of signal loss caused by thick window thickness. Summary of the Invention

[0005] The purpose of this invention is to address the aforementioned problems in the prior art by providing an oxygen-free circulating liquid cell and in-situ characterization method for high-resolution X-ray diffraction using a horizontal goniometer. This is achieved by designing an oxygen-free circulating liquid cell (suitable for vertical installation of a horizontal goniometer) containing a modified sealing screw (with a built-in elastic conductive copper column and an electro-hydraulic isolation O-ring), a thin-gauge Kapton membrane (1~100μm), and a conductivity extension interface. Combined with N2 pre-deoxygenation of the electrolyte, precise XRD optical path calibration (Z scan + Rocking curve optimization), and a simultaneous electrochemical-high-resolution XRD-conductivity testing method, high-precision dynamic tracking of the microstructure evolution of functional thin film materials during oxygen-sensitive electrochemical processes under electro-driven conditions is realized.

[0006] To achieve the above-mentioned objectives, the present invention employs the following technical solution: an oxygen-free circulating liquid pool for high-resolution X-ray diffraction using a horizontal goniometer comprises:

[0007] The cell body is adapted to the sample holder drive plate of the horizontal goniometer high-resolution X-ray diffraction equipment and has a vertical installation structure; the main cavity of the cell body is provided with an electrolyte inlet, an electrolyte outlet, at least three electrode interfaces and through holes, and the electrode interfaces are used to install the working electrode, counter electrode and reference electrode.

[0008] The X-ray window is covered with a thin film that can penetrate X-rays. It is detachably connected to the pool body and forms a sealed space when it is fixed together with the pool body.

[0009] The sample holder, located within the main cavity of the pool, is used to hold the substrate sample.

[0010] The sealing screw is located at the bottom of the pool. It has a hollow structure and an internal elastic conductive element. The top of the elastic conductive element is surrounded by a liquid-electric isolation element. The sealing screw is used to push the sample on the sample holder through the through hole to press it stably against the elastic conductive element and to achieve isolation between the liquid circuit and the electrical circuit.

[0011] The conductivity detection interface reuses a sealed screw and an elastic conductive component to synchronously acquire the conductivity signal of the sample.

[0012] The base, located at the bottom of the pool, is used to fix the pool to the electric base of the horizontal goniometer high-resolution X-ray diffraction equipment and is adapted to adjust the height of the pool.

[0013] Furthermore, the thin film covering the X-ray window is a Kapton film with a thickness of 10~100μm.

[0014] Furthermore, the elastic conductive component is a copper spring or conductive copper pillar arranged diagonally, and the electro-hydraulic isolation component is a sealing ring.

[0015] Furthermore, it also includes a counter electrode diaphragm accessory disposed between the counter electrode and the main cavity of the pool body, for isolating the counter electrode cavity from the main cavity.

[0016] Furthermore, the pool also includes a metal cover and PEEK screws. The metal cover covers the outside of the X-ray window, and the PEEK screws are used to fix the metal cover to the pool.

[0017] The in-situ electrochemical catalysis high-resolution X-ray microstructure characterization method for an oxygen-free circulating liquid pool, as described above, includes the following steps:

[0018] S1: Assemble the oxygen-free circulating liquid cell, place the sample with the deposited functional thin film material on the sample holder, push the sample to press against the elastic conductive part through the sealing screw, and connect the working electrode, counter electrode and reference electrode.

[0019] S2: After deoxygenating the electrolyte, the oxygen-free electrolyte is pumped into the tank through the electrolyte inlet and flows out through the electrolyte outlet to form a circulation. Pre-circulation is used to confirm that there is no leakage.

[0020] S3: The assembled oxygen-free circulating liquid pool is vertically fixed to the electric base of the horizontal goniometer high-resolution X-ray diffraction equipment via the base, and the height of the pool is adjusted to match the optical path of the equipment.

[0021] S4: The X-ray beam path and sample position are calibrated by performing Z-scan to center the cell in the beam path, Rocking curve scan to make the cell surface parallel to the beam path, incident angle optimization, and 2theta-omega scan to locate the thin film peak.

[0022] S5: Apply a preset external electric field to the working electrode, and simultaneously start high-resolution X-ray diffraction test and conductivity signal acquisition. In real time, acquire X-ray high-resolution diffraction data and conductivity data of functional thin film materials during the oxidation-reduction process under inert gas protection, and analyze the microstructure evolution and macroscopic electrical properties of the material.

[0023] Furthermore, in step S2, the deoxygenation treatment adopts an inert gas bubbling method, and the inert gas is nitrogen; the electrolyte is an alkaline electrolyte, an acidic electrolyte, or a neutral electrolyte.

[0024] Furthermore, in step S4, the incident angle optimization is performed as follows: the Z-axis height of the sample stage is lowered by 0.5~1mm, the step size is 0.1mm / step, the 2theta angle is fixed as the theoretical 2theta peak position of the substrate, a rocking scan is performed and the omega angle when the intensity is maximum is recorded as the incident angle.

[0025] Furthermore, in step S4, the 2theta-omega scan range is 42~49°, the scan step size is 0.01° / step, and the scan time is 0.1s / step.

[0026] Furthermore, in step S5, a preset external electric field is applied through an electrochemical workstation, and the high-resolution X-ray diffraction test adopts a continuous acquisition mode. The acquired diffraction data includes one-dimensional 2-theta-omega spectral lines and two-dimensional 2-theta-omega spectral lines.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. Filling a technological gap and achieving precise measurement: This invention provides for the first time a systematic method for high-resolution in-situ XRD testing of vertically mounted flowing liquid pools on a horizontal goniometer. It innovatively solves the key technical problem of signal loss caused by window bulging, making it possible to perform precise in-situ structural characterization of oxygen-sensitive electrochemical processes. It constructs an electrocatalytic process with multi-field coupling of inert gas atmosphere and applied electric field, and realizes real-time tracking of structural evolution caused by liquid-solid interface reaction through high-resolution in-situ detection of X-rays.

[0029] 2. High data reliability: Through innovative sealing screw design, O-rings are used to achieve physical isolation between the conductive post (which can be an inert metal such as copper, gold, or tantalum) and the electrolyte, fundamentally eliminating side reactions and parasitic currents caused by contact between conductive components and electrolyte. Combined with electrolyte circulation under inert gas protection, the purity and high reliability of electrochemical and structural data are ensured.

[0030] 3. Significantly improved signal quality: The use of a 10~100μm thin Kapton film to replace the traditional 120μm thick film significantly reduces X-ray absorption and significantly improves signal transmittance and signal-to-noise ratio, making it possible to detect weak structural changes at the sub-angstrom level and improving the sensitivity and accuracy of the measurement.

[0031] 4. Broader research dimensions: The in-situ environment of multi-field coupling between the constructed inert gas atmosphere and the applied electric field successfully realized the in-situ visualization of the atomic-level structure evolution in the electrocatalytic process under the coexistence of gas, liquid and solid phases; the device integrates an extended interface for in-situ conductivity testing, which can simultaneously acquire information on the atomic-level structure, electrochemical and electrical dimensions of materials in the same system, providing a more powerful analytical means for revealing the structure-activity relationship and reaction mechanism of complex materials.

[0032] 5. Strong applicability and scalability: The design of this solution has good compatibility. It is not only applicable to thin film materials, but can also be easily extended to various forms of samples such as bulk materials and powder electrodes. It has broad industrial applicability and application prospects in the fields of new energy, semiconductors and catalysis. Attached Figure Description

[0033] Figure 1 This is a structural schematic diagram according to an embodiment of the present invention;

[0034] Figure 2 This is a schematic diagram of the structure of the sealing screw according to an embodiment of the present invention;

[0035] Figure 3 This is a schematic diagram of a liquid pool vertically mounted on an X-ray diffraction device according to an embodiment of the present invention;

[0036] Figure 4 This is a 2-theta-omega scan spectrum of the substrate and thin film according to an embodiment of the present invention (the vertical axis represents intensity, not labeled).

[0037] Figure 5 This is a graph of the applied voltage over time at an electrochemical workstation according to an embodiment of the present invention;

[0038] Figure 6 This is a 2-theta-omega scan one-dimensional spectral map of the substrate and thin film in an in-situ environment according to an embodiment of the present invention.

[0039] Figure 7 This is a 2-theta-omega scanning two-dimensional spectrum of the substrate and thin film in an in-situ environment according to an embodiment of the present invention.

[0040] In the diagram, 1. Liquid cell; 2. Sample holder; 3. Working electrode; 4. Reference electrode; 5. Counter electrode; 6. Counter electrode diaphragm accessory; 7. Working electrode extension line; 8. Conductivity detection line; 10. X-ray diffraction equipment; 11. Cell body; 111. Electrolyte outlet; 112. Electrolyte inlet; 12. Metal cover; 13. Kapton membrane; 14. Sealing screw; 141. Copper pillar; 142. Sealing ring; 15. Base; 16. Piston; 17. Peek screw; 101. Sample holder drive plate. Detailed Implementation

[0041] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.

[0042] The following is in conjunction with the appendix Figure 1-3 Taking "In-situ characterization of LaxSr1-xFeO3 functional thin films deposited on SrTiO3 substrates" as an example, this paper details the specific implementation of the present invention. In this embodiment, the LaxSr1-xFeO3 thin film is a typical oxygen-sensitive proton conductor, commonly used in the cathode of solid-state batteries. Its electrically driven proton insertion / extraction (redox) process is easily interfered with by oxygen, which can fully verify the technical effect of the present invention. The equipment used includes: a horizontal goniometer, a high-resolution X-ray diffractometer (XRD), an electrochemical workstation, a peristaltic pump, and a conductivity meter.

[0043] Example 1: Specific assembly of the anaerobic circulating liquid tank 1

[0044] 1. Selection and parameters of core components:

[0045] Cell body 11: Made of polyetheretherketone (PEEK), with overall dimensions of 50mm × 30mm × 20mm (length × width × height), adapted to the sample holder drive plate 101 of the XRD instrument; the main cavity of cell body 11 has a mounting groove for mounting the sample holder 2, an electrolyte inlet 112 with a diameter of 2mm, an electrolyte outlet 111 with a diameter of 2mm, and three electrode interfaces (corresponding to the working electrode 3 (the working electrode 3 is also equipped with a working electrode extension line 7), the counter electrode 5, and the reference electrode 4, mainly for connecting wires). These are all connected to the mounting groove, and a through hole is provided in the center of the mounting groove to allow the sealing screw 14 to pass through. The shape of cell body 11 is not limited here.

[0046] X-ray window: A metal cover 12 with openings is used, and a 50μm thick X-ray window film, such as Kapton film 13 (e.g., model DuPont Kapton HN), is selected. The film is fixed to the pool body 11 by passing through the Kapton film 13 with Peek screws 17 to ensure that the film is flat and wrinkle-free (to avoid affecting X-ray penetration).

[0047] The sealing screw 14 is made of PEEK and has two 1mm diameter copper springs or copper pillars 141 (elastic conductive elements) arranged diagonally inside. Two fluororubber O-rings 142 (hydraulic-electrical isolation elements) are fitted at the top of the sealing screw 14. It can be rotated to achieve a micro-displacement adjustment of ±2mm. This allows it to pass through the through-hole at the bottom of the tank 11, lifting the sample holder 2 upwards, achieving stable contact between the sample on the sample holder 2 and the elastic conductive element, and isolating the liquid circuit from the electrical circuit. Preferably, the elastic conductive element is a copper pillar 141, with a structure similar to the elastic contacts on existing chargers; the specific structure will not be described in detail. Furthermore, other materials with better conductivity and elasticity can be used, and can be replaced as needed.

[0048] Sample holder 2: Installed in the main cavity of the pool body 11, used to hold the substrate sample.

[0049] Counter electrode diaphragm accessory 6: used to be installed on the side wall of the pool body 11 by screws, used to isolate the counter electrode 5 cavity from the main cavity, and to prevent the Pt wire from directly contacting the electrolyte in the main cavity and causing side reactions.

[0050] Electrodes: The working electrode 3 is a 1cm×1cm LaxSr1-xFeO3 / SrTiO3 epitaxial film (LaxSr1-xFeO3, film thickness 80 nm), with a piston 16 that can be placed below it. The piston 16 is used to support the sample (if the sample is very thick, the piston 16 can be removed; if the sample is very thin, the piston 16 is used to support the sample to adapt to the height during testing); the counter electrode 5 is a 0.5 mm diameter Pt wire (5 cm in length, one end inserted into the cell body 11, and the other end connected to the electrochemical workstation); the reference electrode 4 is an Hg / HgO electrode (1 mol / L KOH electrolyte, with the electrode interface sealed with 3 layers of polytetrafluoroethylene waterproof tape).

[0051] Conductivity detection interface: The copper column 141 inside the reusable sealing screw 14 is in contact with the sample at one end and connected to the conductivity tester through the conductivity detection line 8 at the other end to realize synchronous acquisition of conductivity signal.

[0052] Silicone base 15: 5 mm thick, with grooves on the surface that match the bottom of the pool body 11. The pool body 11 is fixed to the electric base 15 (sample rack drive plate 101) of the XRD equipment by high-temperature resistant double-sided tape or screws.

[0053] 2. Assembly steps for pool body 11:

[0054] Take the counter electrode diaphragm accessory 6 and install it inside the counter electrode 5 interface of the pool body 11 to ensure complete coverage of the interface and prevent the main cavity from communicating with the counter electrode 5 cavity.

[0055] LaxSr1-xFeO3 / SrTiO3 thin film sample (working electrode 3) is laid flat on the sample holder 2 at the top of the sealing screw 14, with the sample test surface facing upwards;

[0056] Cover with a 50 μm thick Kapton membrane 13, then cover with a metal cover 12 (such as 304 stainless steel), and tighten symmetrically with 8 M3 Peek screws 17 to fix the metal cover 12 (the torque is controlled at 0.5 N·m to avoid excessive compression and deformation of the Kapton membrane 13).

[0057] Slowly rotate the sealing screw 14 to push the sample holder 2 upward until the sample contacts the copper column 141; at the same time, monitor the open circuit voltage (OCP) and AC impedance spectrum (EIS, frequency range 100 kHz~0.01 Hz) through the electrochemical workstation: when the OCP fluctuation is stable at 2~18 mV (≤20 mV) and the ohmic impedance is 28~32Ω (average 30 Ω, in the range of 10~50Ω), the electrical contact is judged to be good;

[0058] Insert the Pt counter electrode 5 and the Hg / HgO reference electrode 4 respectively, and wrap the gap between the electrode and the interface of the pool body 11 with polytetrafluoroethylene waterproof tape (wrapping width 5mm) to ensure a seal without leakage.

[0059] Connect the electrolyte inlet 112 and outlet to the peristaltic pump and electrolyte storage beaker through silicone tubes (1mm inner diameter) to complete the assembly of the sample cell (anaerobic circulating liquid cell 1).

[0060] Example 2: Implementation of in-situ electrochemical-high-resolution XRD characterization method

[0061] Based on the same concept, this embodiment uses the oxygen-free circulating liquid cell 1 from Embodiment 1 to detect the substrate sample. The specific steps are as follows:

[0062] S1. Assemble the sample cell of Example 1;

[0063] The in-situ environment of multi-field coupling between the constructed inert gas atmosphere and the applied electric field successfully realized the in-situ visualization of the atomic-level structure evolution process in the electrocatalysis process under the coexistence of gas, liquid and solid phases; the process was carried out according to the steps disclosed in Example 1.

[0064] S2, Electrolyte deoxygenation and circulation

[0065] Prepare a 0.1 M KOH electrolyte (e.g., ultrapure water as solvent, resistivity 18.2 MΩ·cm) and pour it into a 500 mL beaker;

[0066] Insert an N2 tube (99.999% purity) to the bottom of the beaker and bubble at a flow rate of 50 mL / min for 30 minutes to complete deoxygenation (the dissolved oxygen content in the electrolyte is ≤0.1 mg / L as measured by a dissolved oxygen meter).

[0067] Start the peristaltic pump and set the flow rate to 20~1000 μL / min. Pump the anaerobic KOH electrolyte into the tank 11 through the inlet and then return it to the beaker through the outlet. At the same time, continuously introduce N2 into the beaker (reduce the flow rate to 10 mL / min to maintain an anaerobic environment).

[0068] After continuous circulation for 1 hour, observe that there is no liquid dripping at the interface between the silicone tube and the pool body 11. If there is no leakage, stop the peristaltic pump and put it on standby.

[0069] S3, Pool 11 Installation and Optical Path Alignment

[0070] The anaerobic circulating liquid tank 1 assembled in Example 1 is fixed to the electric base 15 of the XRD equipment using double-sided adhesive or screws on the silicone base 15.

[0071] Turn on the XRD laser positioning system (wavelength 632.8 nm), and manually adjust the Z-axis height of the motorized base 15 (adjustment range -2~2 mm) on the control software provided with the XRD equipment until the laser beam is focused on the center of the sample under the Kapton film 13, and confirm that the X-ray window is aligned with the optical path.

[0072] S4. Optical path and sample position calibration

[0073] (1) Z-scan calibration (optical path center positioning)

[0074] Enable the XRD light intensity monitoring function, set the X-ray tube voltage to 50 kV and the current to 50 mA, and the Cu target (wavelength 1.5406 Å).

[0075] The Z-axis of the control electric base 15 is moved from -1 mm to 2 mm (step size 0.1 mm), and the X-ray intensity of the detector is recorded in real time. When the intensity reaches 50% of the maximum intensity, the cell 11 is at the center of the optical path (half of the light is cut off), and the initial height of the Z-axis is recorded as 0.5 mm.

[0076] (2) Rocking curve calibration (the surface of pool 11 is parallel to the optical path)

[0077] The 2θ angle of the XRD detector was set to the theoretical value of 46.472° for the 002 peak of the SrTiO3 substrate, and the Rocking scan was started (omega angle scan range -0.5°~0.5°, step size 0.005°, scan speed 0.1° / min).

[0078] Synchronously adjust the Z-axis height (0.05 mm each time) until the peak intensity of the Rocking curve reaches its maximum value. Record the omega angle as 23.15° and the Z-axis height as 1.1 mm at this time, and determine that the surface of the pool body 11 is parallel to the optical path.

[0079] (3) Optimization of incident angle

[0080] With the detector's 2theta angle fixed at 46.472°, the Z-axis height was gradually increased from 1.1 mm to 1.5 mm (total increase distance 0.4 mm, step size 0.1 mm).

[0081] For every 0.1 mm decrease, a Rocking scan is performed (range 22.5°~24°, step size 0.005°), and the peak intensity of each scan is recorded; when the Z-axis height is 1.4 mm, the Rocking peak intensity is the largest, and the omega angle of 23.30° at this time is recorded as the final incident angle.

[0082] (4) Functional thin film peak positioning

[0083] The XRD scanning mode was set to 2-theta-omega scanning, with a scanning range of 42°~49°, a step size of 0.01°, and a scanning time of 0.1 s / step. The X-ray tube parameters remained unchanged.

[0084] like Figure 4 As shown, a scan was initiated, and a 002 peak was detected in the LaxSr1-xFeO3 thin film at 2theta = 45.6°, and in the SrTiO3 substrate at 46.472°, completing the peak localization. The presence of fringe satellite peaks in the thin film indicates that the film has achieved epitaxy on the substrate and has good crystal quality.

[0085] S5, Synchronous In-situ Testing

[0086] Restart the peristaltic pump (flow rate 1 mL / min) to maintain electrolyte circulation (to achieve liquid deoxygenation, N2 should be introduced into the liquid for at least 30 minutes beforehand, then start introducing liquid, selecting an appropriate flow rate as needed, and simultaneously performing a 2theta-ω test to determine if there are any significant changes in the sample peaks); due to the change in liquid film thickness caused by the introduction of liquid, the substrate and thin film peaks may disappear at this time, so it is necessary to manually fine-tune the sample stage height according to the thin film peak intensity, and combine the rocking of the substrate peak to determine the scanning parameters after adding liquid. After confirming that there are no errors, the in-situ XRD test can be started normally.

[0087] like Figure 5 As shown, the voltage program is set at this time, and the XRD acquisition strategy program is set simultaneously to continuously acquire XRD spectra. Figure 6 To achieve in-situ X-ray tracking of microstructures under synchronous voltage application in an in-situ environment. Figure 7 ).like Figure 6 As shown, in-situ XRD tests reveal that, under the applied negative voltage, a series of one-dimensional spectra obtained from in-situ monitoring show that the peak positions of the thin film shift towards lower angles, and the interplanar spacing increases (calculated using the Bragg diffraction formula 2d sin θ = nλ). This indicates that the atomic-level structure undergoes lattice expansion during the reduction process of intercalated protons. The shift of the 2θ angle towards lower angles during this reduction process leads to increased interplanar spacing and lattice expansion, which is very intuitively observed from… Figure 7The film was obtained from the above, and the fringe satellite peak was retained during the reduction process, indicating that the film still maintained very good crystal quality during the proton intercalation process.

[0088] III. Verification of Test Results

[0089] This embodiment utilizes the aforementioned apparatus and method to achieve simultaneous in-situ electrochemical-high-resolution XRD-conductivity characterization of LaxSr1-xFeO3 functional thin films in an oxygen-free flowing electrolyte:

[0090] Environmental control effect: The dissolved oxygen content was always ≤0.1mg / L during the electrolyte circulation process, and there were no side reaction signals, proving that the oxygen isolation was effective;

[0091] Structural resolution: lattice parameter variation of 0.02 Å (sub-angstrom level) was captured, and the XRD peak signal-to-noise ratio was improved by 3 to 5 times (compared to 120 μm Kapton film 13).

[0092] Multi-dimensional correlation: The change in conductivity is consistent with the trend of lattice expansion, which verifies the correlation mechanism of "proton embedding-structural change-transport performance". The in-situ environment of multi-field coupling between the constructed inert gas atmosphere and the applied electric field successfully realizes the in-situ visualization of the atomic-level structure evolution process in the electrocatalysis process under the coexistence of gas, liquid and solid phases, which meets the actual application scenario requirements of solid-state batteries.

[0093] Based on the above embodiments, those skilled in the art can replace the sample with a block of LiCoO2 (for lithium-ion batteries) or powdered Ni(OH)2 (for nickel-metal hydride batteries) with flat upper and lower surfaces. Only by adjusting the size of the sample holder 2 (the diameter of the block sample holder 2 is 10 mm, and the powder sample holder 2 has a pressing structure) and the electrolyte type (such as 1M LiPF6 / EC-DMC for LiCoO2), in-situ characterization of similar oxygen-sensitive systems can be achieved, fully demonstrating the compatibility and scalability of the present invention.

[0094] The parts of this invention not described in detail are prior art, therefore they are not described in detail here.

[0095] Those skilled in the art should understand that, in the disclosure of this invention, the terms "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the above terms should not be construed as limiting this invention.

[0096] It is understood that the term "a" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element can be one, while in another embodiment, the number of the element can be multiple, and the term "a" should not be understood as a limitation on the number.

[0097] Although this document frequently uses terms such as liquid cell 1, sample holder 2, working electrode 3, reference electrode 4, counter electrode 5, counter electrode diaphragm accessory 6, working electrode extension line 7, conductivity detection line 8, X-ray diffraction equipment 10, cell body 11, electrolyte outlet 111, electrolyte inlet 112, metal cover 12, Kapton membrane 13, sealing screw 14, copper column 141, sealing ring 142, base 15, piston 16, Peek screw 17, and sample holder drive plate 101, the possibility of using other terms is not excluded. The use of these terms is merely for the convenience of describing and explaining the essence of the invention; interpreting them as any additional limitation would contradict the spirit of the invention.

[0098] This invention is not limited to the preferred embodiments described above. Anyone can derive other products in various forms under the guidance of this invention. However, regardless of any changes made to their shape or structure, any technical solution that is the same as or similar to this invention falls within the protection scope of this invention.

Claims

1. An oxygen-free circulating flow liquid cell for high resolution X-ray diffraction analysis using a horizontal goniometer, characterized in that, The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction.

2. An oxygen-free, circulating flow liquid bath according to claim 1, wherein, The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction.

3. An oxygen-free, circulating flow liquid bath according to claim 1, wherein, The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction.

4. An oxygen-free, circulating flow liquid bath according to claim 1, wherein, The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction.

5. An oxygen-free, circulating flow liquid bath according to claim 1, wherein, The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction.

6. The in-situ electrochemically catalyzed high-resolution X-ray microstructure characterization method of an oxygen-free circulating flow liquid cell according to any one of claims 1-5, characterized in that, The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction.

7. The in-situ electrochemical catalysis high-resolution X-ray microstructure characterization method according to claim 6, characterized in that, The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application relates to a liquid cell for a horizontal goniometer high-resolution X-ray diffraction device, and belongs to the technical field of X-ray diffraction. The application 8. The in-situ electrochemical catalysis high-resolution X-ray microstructure characterization method according to claim 6, wherein, In step S4, the incident angle is optimized by lowering the sample stage Z-axis height by 0.1-1 mm, lowering step length is 0.1 mm / step, fixing the 2theta angle as the theoretical 2theta peak position of the substrate, performing Rocking scanning and recording the omega angle at the maximum intensity as the incident angle.

9. The in-situ electrochemical catalysis high-resolution X-ray microstructure characterization method according to claim 6, wherein, In step S4, the 2theta-omega scanning range is 42-49°, scanning step length is 0.01° / step, and scanning time is 0.1 s / step.

10. The in-situ electrochemical catalysis high-resolution X-ray microstructure characterization method of claim 6, wherein, In step S5, the preset external electric field is applied by an electrochemical workstation, the high-resolution X-ray diffraction test adopts a continuous acquisition mode, and the acquired diffraction data includes one-dimensional 2theta-omega spectrum and two-dimensional 2theta-omega spectrum.

Citation Information

Patent Citations

  • Electrochemical pool of open-type simulation lithium battery capable of observing state change of electrode material during charge-discharge process in in-situ way and test method

    CN110265741A

  • Design and test method of in-situ XRD (X-Ray Diffraction) micro-electrolytic tank of foam metal electrode

    CN117269210A